Directional water navigation and reallocation in Tillandsia capitata - Jiaoyuan Lian; Wei Li; Ling Yang; Hegeng Li; Qiyu Deng; Hengjia Zhu; Yiyuan Zhang; Nicholas X. Fang; Liqiu Wang (Proceedings of the National Academy of Sciences, 2025)
Liquid manipulation is ubiquitous in nature and engineering, enabling controllable and efficient liquid delivery. Conventional understanding of liquid manipulation relies on inhomogeneous chemical modifications or single-scale structure design. Here, we present how water is directionally navigated and spontaneously reallocated at high efficiency via the cross-scale topology on Tillandsia capitata leaves. These leaves feature transversely curved lanceolate macrostructures decorated by a layer of microtrichomes with varied morphologies. The macrostructure creates a lanceolate effect in the transport direction for fundamental navigation. At the same time, the microtrichomes serve dual functions: constructing a self-wetting superhydrophilic surface to facilitate the water transport speed and implementing water spreading in the opposite direction for autonomous reallocation. We explain the multiscale transport behavior through theoretic analysis and finite element simulations. Our findings demonstrate how cross-scale topographies jointly function in efficient autonomous fluid manipulation, with potential applications such as droplet driving, fog harvesting, and seawater desalination, offering pathways for improving liquid processing efficiency and reducing energy consumption.